Childhood psychosocial adversity and female reproductive timing: a cohort study of the ALSPAC mothers. Issue 1 (9th November 2017) - Magnus, Maria C; Anderson, Emma L; Howe, Laura D; Joinson, Carol J; Penton-Voak, Ian S; Fraser, Abigail
Abstract : Background: Previous studies of childhood psychosocial adversity and age at menarche mostly evaluated single or a few measures of adversity, and therefore could not quantify total psychosocial adversity. Limited knowledge is currently available regarding childhood psychosocial adversity in relation to age at menopause and reproductive lifespan. Methods: We examined the associations of total and specific components of childhood psychosocial adversity with age at menarche (n=8984), age at menopause (n=945), and length of reproductive lifespan (n=841), in mothers participating in the Avon Longitudinal Study of Parents and Children. We used confirmatory factor analysis to characterise lack of care, maladaptive family functioning, non-sexual abuse, overprotective parenting, parental mental illness and sexual abuse. These specific components of childhood psychosocial adversity were combined into a total psychosocial adversity score using a second-order factor analysis. We used structural equation models to simultaneously conduct the factor analysis and estimate the association with the continuous outcomes of interest. Results: Total childhood psychosocial adversity was not associated with age at menarche, age at menopause or length of reproductive lifespan. When we examined the separate psychosocial adversity constructs, sexual abuse was inversely associated with age at menarche, with a mean difference of −0.17 (95% CI −0.23 to −0.12) years per SD higher factor score, and with age at menopause, with a mean difference of −0.17 (95% CI −0.52 to 0.18) per SD higher factor score. Conclusion: Childhood sexual abuse was associated with lower age at menarche and menopause, but the latter needs to be confirmed in larger samples.